Pretreatment neutrophil-to-lymphocyte ratio is associated with immunotherapy efficacy in patients with advanced cancer: a systematic review and meta-analysis - Jialin Su; Yuning Li; Shuhua Tan; Tianli Cheng; Yongzhong Luo; Lemeng Zhang (Scientific Reports)
Abstract This study aimed to systematically investigate the value of the pre-treatment neutrophil-to-lymphocyte ratio (NLR) in prognosticating the outcome of patients with advanced cancer receiving immunotherapy. We searched Embase, PubMed, Web of Science, and Cochrane Library to identify studies about cancer patients with immunotherapy until November 29, 2024. Retrospective or prospective cohort studies with pretreatment NLR data were included. The odds ratio (OR) and 95% confidence interval (CI) were calculated to evaluate the predictive value of NLR in prognosis and immunotherapy efficacy. The random effect model was applied for meta-analysis and the risk of bias was assessed by Egger test and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method. A total of 129 articles involving 18780 cases were finally selected. Most cases were advanced cancers with the median follow-up period ranged 2–48.6 months. The high pretreatment NLR level was associated with the significantly reduced OS (HR (95%CI) = 2.26 (2.03, 2.53)), PFS (HR (95% CI) = 1.83 (1.69, 1.98)), ORR (OR (95%CI) = 0.53 (0.46, 0.61)) and DCR (OR (95% CI) = 0.36 (0.29, 0.43)) in patients with advanced cancer receiving immunotherapy. The quality of evidence was low, attributed to the serious risk of bias and incon¬sistency. An elevated NLR before immunotherapy was significantly associated with poor clinical outcomes in patients with advanced cancer.